Linkage Between Stock Market and Foreign Exchange Market in Brics - Theivanayaki, M.; Keong, Ooi Chee; Ganeshwari, M. (International Journal of Psychosocial Rehabilitation, 2020)
This paper attempts to examine whether or not a causal relationship exists between foreign exchange rates and stock market in BRICS. By applying the techniques of Granger Causality test and Co-integration test, relationships between both these markets were determined for data between 2009 and 2019. The Granger causality test result there exist unidirectional relationship between Russia, India, China and South Africa. Co-integration test results long run relationship exist for India and China. Further, the study suggest that these results would be helpful for the investor to predict one market by using the information of other market and also will help financial managers to obtain decision relating to portfolio diversification.